Predictors of early readmission in chronic heart failure : REFERENCE (pREdictors oF Early REadmission iN Chronic hEart failure) - Barbosa, Mário Augusto Rodrigues Teixeira, 1980- (2019)
Tese de mestrado, Doenças Metabólicas e Comportamento Alimentar, Universidade de Lisboa, Faculdade de Medicina, 2019